Penggunaan Bahasa Slang pada Postingan dan Kolom Komentar Media Sosial X di Era Gen Alpha - Syarifah Salwa; Nadine Andara; Salma Syakira; Sheren Tsabita Aqilah; Putri Mazaya Andika (Pusat Riset dan Inovasi Nasional, 2024)
Slang is an informal language that is the result of individual or group creativity that is accepted and used by the wider community. Slang language among Generation Alpha emerged as a result of interactions on social media with the previous generation, namely Generation Z. Data collection methods were carried out by reading, taking notes and recording (screenshots). Researchers also counted how many times the slang language appeared on social media from the most frequently to the least frequently used in October 2024. In that period, 3,728 mewing words, 3,410 sigma words, 3,038 sus words, 2,666 skibidi words, 2,275 slay words, 1,705 flexing words, 152 fanum tax words, and 90 words looksmaxing in posts and comments columns on X's social media in Indonesia. Slang is divided into four forms, namely abbreviations, interjections, funny mispronunciations, and shortened forms.